The Use of Wordwall Learning Media with a Food Security Orientation in Teaching Procedure Text to Elementary School Students - Lavella Adenia Finan Irawan; Nurul Istiq'faroh; M. Bambang Edi Siswanto; Wasis Suprapto (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
This study aims to determine the practicality of the food security-oriented interactive learning media Wordwall in teaching procedure text to elementary school students. The study used the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) to test its practicality. The research subjects consisted of 22 third-grade students at SD Negeri 194 Gresik. Data were collected through teacher and student response questionnaires using a Likert scale to measure the clarity of the material, the practicality of the media, and its usefulness. The results of the analysis showed that the Wordwall media received a practicality rating of 90% from teachers and 87% from students, both of which fall into the “very practical” category. Analytically, these findings indicate that the developed media are not only suitable for use from a technical learning perspective but also effective in increasing teachers' and students' participation in procedure text material. The high level of positive feedback from teachers indicates that the media is easy to implement in the learning process without requiring complex technical adaptations, while students' feedback shows improved ease of understanding the material through an interactive approach. Thus, these results confirm that the food security-oriented Wordwall contributes as a learning medium that supports the integration of Sustainable Development Goal 2 (Zero Hunger). However, this study has limitations due to the relatively small sample size and a scope limited to practicality without quantitatively measuring effectiveness in improving learning outcomes. Therefore, future research is recommended to expand the sample size, test the effectiveness of the media, and evaluate its impact on student learning outcomes.